Gestión de las prácticas pre-profesionales en el desarrollo institucional de la unidad educativa san José “La Salle” del cantón Latacunga provincia de Cotopaxi, en el período 2015-2016.” manual de gestión de prácticas pre-profesionales. - Bombón Toapanta, Verónica Janeth (2017)
The research purpose is to generate an internship proposal due to at present, the internship is a requirement for university students of all specialties, taking into account that the Professional Training must attenuate the fusion of Theory - Practice, in such a way, students incorporated new knowledge linked to the profession; Developing and strengthening competencies related to labor demands. Information gathered as the theoretical basis of scientific research, including arguments concerning Vocational Training, internship emphasizes educational, social, cultural and historical sources of information. Within the research methodology, the tools used for the investigation are clearly explained, from which it obtains precise data, focused on a possible solution. Finally, a survey will be applied to teachers; and the interview to obtain information about internship development at San José "La Salle" school. It is proposed that an internship Handbook is developed in order to improve the Educación Básica internship career in which three main process factors are included: University, Practitioners and school.